2013
DOI: 10.1111/jace.12174
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray Diffraction Study of the Effect of High‐Temperature Heat Treatment on the Microstructural Stability of Third‐Generation SiC Fibers

Abstract: Third‐generation SiC fibers [High Nicalon S (HNS) and Tyranno SA3 (Ty–SA3)] were studied by X‐ray diffraction and transmission electron microscopy (TEM) after heat treatments in neutral atmosphere up to 1900°C. The microstructural changes in both materials were determined using a modified Hall–Williamson method introducing an anisotropy parameter taking into account the high density of planar defects. HNS fibers exhibit significant modifications in the coherent diffraction domains (CDD) size, which drastically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
(60 reference statements)
1
21
0
Order By: Relevance
“…The Hi-Nicalon Type S fiber is composed of SiC grains with some free carbon, generally containing a turbostratic texture, located between SiC grains [20]. Previous studies have shown that the fiber microstructures display virtually no evolution from temperature alone up to $1600°C.…”
Section: Resultsmentioning
confidence: 99%
“…The Hi-Nicalon Type S fiber is composed of SiC grains with some free carbon, generally containing a turbostratic texture, located between SiC grains [20]. Previous studies have shown that the fiber microstructures display virtually no evolution from temperature alone up to $1600°C.…”
Section: Resultsmentioning
confidence: 99%
“…Hi-Nicalon (S) was developed to be a nearly stoichiometric and highly crystalline SiC fiber. [10,13,[20][21][22][23][24][25][26][27][28] One goal of this paper was to compile all of the oxidation kinetics results that exist to our knowledge in the literature to use as a resource for future SiC fiber oxidation testing and CMC oxidation modeling. [9,11] Several studies on the mechanical properties of SiC are available [12][13][14][15][16][17][18] including a review by Yun and DiCarlo.…”
Section: Sic Fiber Oxidation Literature Reviewmentioning
confidence: 99%
“…These values yield, respectively, 26 and 36 nm for the HNS fibers and 141 and 210 nm for the TSA3 fibers in agreement with Gosset et al . values …”
Section: Experimental Conditionsmentioning
confidence: 99%
“…In this study, we focus on the irradiation behavior of SiC fibers that will be used as reinforcement of the composite, that is, Hi‐Nicalon type S (HNS) from Nippon Carbon Co. (Japan) and Tyranno SA3 (TSA3) from Ube Industries (Japan). These fibers consist of 3C–SiC grains with high stacking fault (SF) densities and small grain sizes . The aim of this work was to study the influence of their different microstructures on their ion‐irradiation behavior in comparison to SiC single crystals.…”
Section: Introductionmentioning
confidence: 99%